School health service activities and their implications to the school health education program of Maasin district I, Southern Leyte - Espina, Anunciacion (Galdo) 1929- ([Quezon City s.n.], 1972)
The study is aimed at looking into the activities of the school health personnel of Maasin I which have been performed in relation to health services. It was concluded that the health activities performed by the health personnel which revolved around the different components of health services were inadequately done as perceived by most of its respondents.
Thesis (M. Ed.)--University of the Philippines.
Keywords: Health education -- Maasin, Southern Leyte